Leaky-Wave antennas with arbitrary radiation based on bianisotropic Huygens’ metasurfaces - Abdo-Sánchez, María Elena; Epstein, Ariel; Eleftheriades, George V. (My University, 2018)
In this contribution, we present the application of Huygens’ metasurfaces (HMS) to the arbitrary design of leaky-wave antennas (LWAs). These metasurfaces have demonstrated their capabiity to tailor the electromagnetic waves at will. We use them to design LWAs consisting on a parallel-plate waveguide in which the top cover is replaced by a HMS, which implements the desired field transformation. By introducing bianisotropy of the omega type into the metasurface, we have the required degrees of freedom to achieve arbitrary control of the LWA radiation parameters: leakage factor and pointing angle (phase constant). The theoretical derivation of the concept and the design methodology will be described. Moreover, the flexibility in the design will be highlighted with results of two examples of broadside radiation with different directivities.
Keywords: Huygens, Principio de; Huygens’ metasurfaces; Leaky-wave antenna